Harmonizing Differentiation and Cost Leadership Strategies in Culinary Businesses - Harahap, Kartini (Research Horizon, 2024)
The culinary business is a sector that continues to grow amidst the challenges of globalization, intense competition, changes in lifestyle, and technological developments. In Indonesia, this sector contributed around 41% of the creative economy's GDP in 2020. In Indonesia, 74% of culinary businesses implement differentiation and cost leadership strategies, but only a small percentage achieve high performance. This shows the challenges in implementing both strategies simultaneously. This research seeks to develop a framework for implementing a combination of differentiation and cost leadership strategies simultaneously in the culinary business. This is done by understanding consumer trends, changing demographics, technology trends, and competition in the market. This research uses qualitative methods with a case study approach to explore the application of differentiation and cost leadership strategies in culinary businesses in the Medan region, North Sumatra. The sample was 47 culinary entrepreneurs who had high performance. Primary and secondary data are used to analyze operational information, costs, and profit margins. The research results show that the integration of differentiation and cost leadership strategies opens up opportunities to create added value for customers while remaining efficient by focusing on unique product quality, operational efficiency, cost control, and experience and value-based marketing so that culinary businesses can succeed in a competitive market.